Pengaruh Bokashi Limbah Sayuran Pasar Terhadap Serapan N Dan Hasil Tanaman Buah Tomat - Serli Jayanti; Saiful Darman; Uswah Hasanah (Universitas Tadulako, 2019)
The results showed that there was an interaction between bokashi and vegetable waste fertilizer on N-soil parameters of 1.02%, plant height of 47.25 cm, number of fruits per plant by 4 pieces, fruit weight per plant of 84.04 g, and fruit diameter per plant is 19.96 mm. This study is an experimental study of Randomized Block Design (RBD) consisting of 6 repeated treatments. a = 0 g / polybag, b = 25 g / polybag (5 tons ha-1), c = 75 g / polybag (15 tons ha-1, d = 125 g / polybag (25 tons ha-1), e = 175 g / polybag (35 tons ha-1), f = 225 g / polybag (45 tons ha-1), g = 275 g / polybag (55 tons ha-1). The purpose of this study was to determine the effect of vegetable waste bokashi on fertilizer on N uptake and tomato fruit yield. The thinking framework is a decrease in tomato production. To overcome this we need balanced fertilization in both organic and inorganic fertilizers. This research was conducted in Donggala Kodi Village. Then it did not significantly affect the parameters of N Absorption plant, wet weight and dry weight of plants.